Writing Anxiety and Academic Procrastination On Undergraduate Thesis Writing: The Role Of Self-Regulation - Agnes Riska Pravita; Paulus Kuswandono (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2022)
Writing anxiety and academic procrastination are said to be interconnected and have a substantial impact on students’ thesis completion. Self-regulation, on the other hand, is what allows students to make progress while writing their thesis. The goal of this research is to find out how writing anxiety and academic procrastination influence students' thesis writing and how they self-regulate themselves to write their thesis. A quantitative study utilizing descriptive statistics was used to conduct this research. Twelve students in a thesis class expressed their consent to participate in the research. The data was gathered by keeping track of the students' thesis writing progress based on word count development on their research drafts, assigning them to write a standardized weekly journal, and delivering two adapted questionnaires from the self-regulation learning strategy survey. The results suggest that the students had a high level of anxiety, with a score of 65.25, with avoidance behaviour being the highest. They also procrastinate on academic revision and review. Goal planning and requesting help, on the other hand, involve their self-regulation the most, whereas task methods and time management engage in the least. Future researchers are urged to do a further in-depth study on this issue since it is worth researching. Lecturers are also urged to introduce students to different reading and writing techniques.